Precision breeding in a changing climate: unlocking resilience through omics and gene editing - Tarali Borgohain; Remya Suma; Mantesh Muttappagol; Banashree Saikia; Arnika Keithellakpam; Adity Laskar; Shridhar Shivakumar Hiremath; Udita Basu; Natarajan Velmurugan; Sudhakar Reddy Palakolanu; Channakeshavaiah Chikkaputtaiah (Functional & Integrative Genomics, 2026)

Locally active memristor–based Chialvo neuron model: bifurcation, multistability, and noise effects - Shivakumar Rajagopal; Fatemeh Parastesh; Viet-Thanh Pham; Karthikeyan Rajagopal; Sajad Jafari (Cognitive Neurodynamics, 2026)

Curcuma caesia-derived carbon quantum dots: Green synthesis, biocompatibility, pharmacological and anti-counterfeiting applications - Sanjana bai Shivaram singh Mahendranath singh; Sushma Mohan; Shivakumar Venkataramaiah; Manjula Mavathur Venkatappa; Vani Karadi Manjappa; Rajesh Rangappa; Bethuru Rangaswamy Radha Krushna; Idagur Somashekar Pruthviraj; Hanumanthappa Nagabhushana; Hosam O. Elansary; Ihab Mohamed Moussa; Muhammad nazim; et al. (Toxicon, 2026)

Collective dynamics and synchronization of coupled hair-bundle models with elastic and viscous interactions - Shivakumar Rajagopal; Fatemeh Parastesh; Karthikeyan Rajagopal; Iqtadar Hussain; Sajad Jafari (Journal of Theoretical Biology, 2026)

Nutritional and hormone fortification of mulberry leaves enhances growth and improves immunity of silkworm larvae (Bombyx mori) to Beauveria bassiana - Subramanian Joshika; Ganesan Shanmugapriya; Kasilingam Balumahendhiran; Muthugoundar Subramanian Shivakumar (Journal of Invertebrate Pathology, 2026)

Patterns and causes of marine mammal strandings along the coast of Karnataka, India - Thejaswini Shettigar; K.C. Prashanthkumar; Shivakumar Haragi (Journal for Nature Conservation, 2026)

A comprehensive review of beneficiation strategies for beach sand minerals - Indraneela Pradhan; Swagat S. Rath; Suchismita Senapati; Shivakumar Angadi (Minerals Engineering, 2026)

Photoperiod-insensitive E1–E4 alleles prolong the reproductive phase and enhance yield in short-season soybean grown in subtropical regions - Nisha Agrawal; Rachana Tripathi; Sanjay Gupta; B. S. Gill; Giriraj Kumawat; Vangala Rajesh; Vennampally Nataraj; Shivakumar Marrana; Milind B. Ratnaparkhe; Gyanesh Kumar Satpute; V. S. Bhatia; Anuradha Bhartiya; et al. (Physiology and Molecular Biology of Plants, 2026)

Drug repurposing in KRAS G12C-mutant NSCLC: a focus on resistance mechanisms and clinical strategies - Anisha Jain; Rafael Rosell; Chandan Dharmashekara; Bhargav Shreevatsa; María González-Cao; Amogha Shivakumar; Shiva Prasad Kollur; Ashwini Prasad; Chandan Shivamallu; M. N. Nagendra Prasad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Comparative exploration of fermentation strategies to amplify arginine deiminase yield from Pseudomonas monteilii - Rajesh Kumar; Srividya Shivakumar (Bioresource Technology Reports, 2026)

Diketopiperazines with In vivo Antimalarial Activity from Sponge-derived Streptomyces sp. 13-12-16 - Loganathan Karthik; Arivarasan Vishnu Kirthi; Anirban Sengupta; Tarun Keswani; Yingxin Li; Shivakumar Banakar; Arindam Bhattachariya; Zhiyong Li (Marine Biotechnology, 2026)

challenging synchronization-based network reconstruction from time series: a critical evaluation using Fitzhugh–Nagumo neural networks - Bahareh Karimi Rahjerdi; Shivakumar Rajagopal; Fahimeh Nazarimehr; Karthikeyan Rajagopal (Biological Cybernetics, 2026)

Exploring the anti-inflammatory activities of Secamone emetica: experimental assays coupled with molecular docking and dynamics - Madhavan Sowmiya; Kuppusamy Selvam; Muthugounder Subaramanian Shivakumar; Chinnamadhu Archana; Poomani Kumaradhas (Vegetos, 2026)

Trends in honey spray drying: A comprehensive analysis of drying conditions, process optimization, physicochemical properties, honey powder enrichment and industrial applications - Rahul Yadav; Sarang Aralkar; K.V. Prasad; D.M. Firake; Pramod Aradwad; D.V.S. Raju; Shivakumar Kv (Trends in Food Science & Technology, 2026)

Rapid flood inundation mapping for dam failure and operations - Shivakumar Balachandran; Parvaneh Nikrou; Ayman Mokhtar Nemnem; Reza Saleh Alipour; Sagy Cohen; Xingong Li; Erfan Goharian; Jasim Imran; Steven J. Burian (Journal of Hydrology, 2026)

Lie symmetry analysis of effluent dispersion over oxytactic-laden porous domain: a mathematical insight on pollutant dynamics - S. P. Shivakumar; S. Areekara; T. V. Smitha; L. Thanuja; S. Devanathan; Ganesh R. Naik; K. V. Nagaraja (Modeling Earth Systems and Environment, 2026)

Influence of D. stocksii bamboo fiber forms and extraction processes on the epoxy matrix composite lamina - B. Vishwash; N.D. Shivakumar; K.B. Sachidananda; Rajath S (Next Research, 2026)

Mapping agroforestry dynamics in central Western Ghats: land cover land use and farmers practices - Shahbaz Noori; H. Tabassum; Shivakumar Inamati (Agroforestry Systems, 2026)

Trade-offs between global warming potential, eco-efficiency and water use efficiency under different establishment methods and nitrogen management strategies for sustainable rice production - S.N. Sandeep; P.S. Fathima; S.B. Yogananda; R. Suma; K.V. Shivakumar; B.S. Sowmyalatha; P. Thimme Gowda; Hanamant M. Halli; Manjanagouda S. Sannagoudar; E. Senthamil; Vinay M. Gangana Gowdra; B. Raghavendra Goud; et al. (Science of The Total Environment, 2025)

Introgression of cyanidin and beta-carotene to develop coloured sweet corn (Zea mays L.) inbreds through marker assisted backcross breeding - Shivakumar Ravichandran; Mohanapriya Balamurugan; Mohammad Reda Ismail; Sivakumar Subbarayan; Kalarani Muthusami; Senthil Alagarsamy; Geethanjali Subramaniam; Vellaikumar Sampathrajan; Ravikesavan Rajasekaran; Karthikeyan Aadhimoolam; Pramesh Khoyumthem; Nepolian Singh Thokchom; et al. (Journal of Cereal Science, 2025)

V2O5-TiO2 SCR Plate Catalysts for High Dust De-NOx Applications: A Comprehensive Characterization Study - S. Rajath; Muzammil Bagewadi; N. D. Shivakumar (Emission Control Science and Technology, 2025)

Development and evaluation of microbial formulations containing Bacillus amyloliquefaciens RP4 and Streptomyces rochei RP7 for the sustainable management of downy mildew in grapes - Rakesh Prakash; Neetha Shivakumar (Journal of Plant Diseases and Protection, 2025)

Geospatial analysis of Agroforestry landscape in the Central Western Ghats, India, using Google Earth Engine - Shahbaz Noori; H. Tabassum; Shivakumar Inamati (Agroforestry Systems, 2025)

Response to letter to editor (P.S Coder and J.D Vidal) regarding “Rodent estrous cycle pattern: Harmonizing the cycle evaluation and interpretation- S. Holalagoudar et al., 2025” - Shivakumar Holalagoudar; Susan Kisielewski; Austin Martini; Kamin Johnson; Anne-Laure Leoni; Corinna Demminger; Sonja Brosel (Regulatory Toxicology and Pharmacology, 2025)

A brief review on natural fiber reinforced composite sandwich structures - B. Vishwash; N.D. Shivakumar; K.B. Sachidananda (Next Research, 2025)

Molecular phylogeny of genus Nothopegia Blume nom.cons. (Anacardiaceae) in Central Western Ghats Karnataka, based on the ITS, rbcL and trnLF markers - Venkatesh Jugal; H.C. Shrishail; P Shivakumar Singh; Kamal Shah; Nagendra Singh Chauhan (Ecological Genetics and Genomics, 2025)

Solvatochromic, DFT Insight into Chemical and Physical Parameters of 4-(4-Nitro-phenoxymethyl)-benzo[h]chromen-2-one (NM2BC) - Shivakumar Chillargikar; Srinath; S. M. Hanagodimath; Omnath Patil; Sulochana Dever (Journal of Fluorescence, 2025)

Investigation of durability characteristics in fiber reinforced geopolymer composite using lathe steel scrap and flexural deformation - Dakka Gurappa; Dushyanth V. Babu R; Shaik Numan Mahdi; M. Shivakumar (Innovative Infrastructure Solutions, 2025)

Co-implementation of deficit irrigation and nutrient management strategies to strengthen soil-plant-seed nexus, water use efficiency, and yield sustainability in fodder corn - Hanamant M. Halli; B.G. Shivakumar; V.K. Wasnik; Prabhu Govindasamy; V.K. Yadav; Sunil Swami; Vinod Kumar; E. Senthamil; Vinay M. Gangana Gowdra; P.S. Basavaraj; K.M. Boraiah; C.B. Harisha (European Journal of Agronomy, 2025)

Skin can Modulate the pH of Topical Creams and Gels - Sanjeevini M; Harini Priya Pa; Rakshitha L; Prajwal N. Murthy; Pragathi S. G; Anusha V. Matadh; Srujana N. Murthy; Srinath R; Shivakumar H. N; Howard Maibach; S. Narasimha Murthy (AAPS PharmSciTech, 2025)

Solvatochromic Study of Coumarin in Pure and Binary Solvents with Computational Insights into Dipole Moment, Reactivity, and Stabilization Energy - Srinath; Shivakumar Chillargikar; S. M. Hanagodimath (Journal of Fluorescence, 2025)

Metrology and manufacturing-integrated digital twin (MM-DT) for advanced manufacturing: Insights from coordinate measuring machine (CMM) and FARO arm measurements - Hamidreza Samadi; Md Manjurul Ahsan; Shivakumar Raman (Next Research, 2025)

Best linear unbiased prediction (BLUP)-based models aided in selection of high yielding charcoal rot and yellow mosaic resistant soybean genotypes - Pawan Kumar Amrate; Vennampally Nataraj; M. Shivakumar; M. K. Shrivastava; Laxman Singh Rajput; Salikram Mohare; Nisha Agrawal; Saloni Mandloi; Kumar Jai Anand; Milind B. Ratnaparkhe; K. Bhojaraja Naik; Sanjay Gupta; et al. (Genetic Resources and Crop Evolution, 2025)

Polyphenol oxidase (PPO) in wheat (Triticum aestivum): a systematic review on bioactivity, inheritance, functionality and their effects on end products - Rajappa Harisha; Adithya P. Balakrishnan; Karthik Kumar Manjunath; Beera Bhavya; Shaily Singhal; Harshitha Bheemapura Shivakumar; Arvind Kumar Ahlawat; Sanjay K. Singh; Anju Mahendru Singh (Cereal Research Communications, 2025)

Experimental and Theoretical Approach to Estimate Electric Dipole Moments and Analysis of Preferential Solvation, Fluorescence Quenching of 4 NPMB Coumarin Molecule by Steady State Method - Srinath; Shivakumar Chillargikar; Omnath Patil; S. M. Hanagodimath (Journal of Fluorescence, 2025)

In vitro, in vivo and in silico anticancer activity and toxicity of Usnic acid extracted from the mycobiont culture of Usnea baileyi - Murugan Mariraj; Mallikarjun Gundappa; Shanmugam Velayuthaprabhu; Kamal Shah; Ponmurugan Ponnuchamy; Suresh Kumar Mendem; P Shivakumar Singh; Nagendra Singh Chauhan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Finite Dose In Vitro Permeation Testing: Significance of Occluding the Donor compartment, a Case study - Prajwal N. Murthy; Mohammad Moinul Hossain; Santanu Kundu; Srinath Rangappa; Shivakumar H. N. (AAPS PharmSciTech, 2025)

Genome-wide identification of copy number variation in diverse black pepper accessions - Parinita Das; T. E. Sheeja; Bibek Saha; A. Fayad; Tilak Chandra; U. B. Angadi; M. S. Shivakumar; T. P. Muhammed Azharudheen; Sarika Jaiswal; Mir Asif Iquebal; Dinesh Kumar (Planta, 2025)

Mutation Analysis of the BRCA1 and BRCA2 Genes in Early-Onset, Familial, and Sporadic Breast Cancer Among the South Indian Population - H. R. Vinoda Kumar; Malligai Elancheran; P. Shivakumar; N. Srinivasan; S. Sushma (Indian Journal of Clinical Biochemistry, 2025)

Exploring potential biological applications of green derived silver nanoparticles using Codiaeum variegatum leaf extract - Arunkumar Lagashetty; M Anusha; Rachana; M Channabasavaraja; Shivakumar; V Veena; R․K Preeti; Sangappa K. Ganiger (Next Research, 2025)

Evaluation of peroxidase mimetic properties of cobalt ferrite (CoFe2O4) nanoparticles and their applications in the assay of aminophenols in water samples - Nelligere Arkeswaraiah Chamaraja; Ningappa Kumara Swamy; Varshini Shivakumar; H. V. Kavya; Mahesh Basavaraju (Nanotechnology for Environmental Engineering, 2025)

Enhancing infiltration rate predictions with hybrid machine learning and empirical models: addressing challenges in southern India - Mooganayakanakote Veeranna Ramaswamy; Hanumapura Kumaraswamy Yashas Kumar; Varshini Jaganatha Reddy; Shivakumar J. Nyamathi (Acta Geophysica, 2025)

Rodent estrous cycle pattern: Harmonizing the cycle evaluation and interpretation - Shivakumar Holalagoudar; Susan Kisielewski; Austin Martini; Kamin Johnson; Anne-Laure Leoni; Corinna Demminger; Sonja Brosel (Regulatory Toxicology and Pharmacology, 2025)

Molecular docking analysis of Ficus religiosa L. fruit extracts with HMG-COA reductase inhibitors, anti-hyperlipidemic effects of its in Albino wistar rats, triggered by Triton-X 100 and High fat diet - Shivakumar Inamdar; Makhmur Ahmad; B. Tazneem; Sana Hashmi; Bhagyalakshmi Kulkarni; Bander M. Aldhabi; Ruqaiya Jamal; Mohamad Taleuzzaman (Bioactive Carbohydrates and Dietary Fibre, 2024)

Structure-based drug design and characterization of novel pyrazine hydrazinylidene derivatives with a benzenesulfonate scaffold as noncovalent inhibitors of DprE1 tor tuberculosis treatment - Shivakumar; P. Dinesha; D. Udayakumar (Molecular Diversity, 2024)

Creating constellations of coexistence through connections between people in human–wildlife conflict areas - Aalayna R. Green; Stotra Chakrabarti; Shweta Shivakumar; Courtney Hughes; Sayan Banerjee; Maureen W. Kinyanjui; Moreangels M. Mbizah; Omar Ohrens; Abigail R. Thiemkey (Conservation Biology, 2024)
Human–wildlife conflict (HWC) is a critical challenge to human development and well‐being and threatens biodiversity conservation. Ideally, HWC mitigation should benefit both wildlife and communities and limit the costs associated with living alongside wildlife. However, place‐ and context‐dependent realizations of conflict are often overlooked in HWC mitigation. Social and systemic dimensions of human–wildlife relationships often receive limited consideration in HWC as a concept and in mitigation strategies implemented globally. In recognizing our collective symmetries as a diverse group of researchers, we pose the idea of constellations of coexistence, based on Atallah et al.’s “constellation of co‐resistance.” Building on literature and our interdisciplinary and cross‐sectoral experiences of working with diverse species inhabiting different sociocultural, sociopolitical, and socioeconomic landscapes, we considered evidence of cultural nuances (e.g., sociocultural dimensions of human–elephant and human–lion interactions in East Africa and India) in HWC mitigation and argue that failing to incorporate them in mainstream practices poses a myriad of ethical and practical consequences. Locally situated but globally relevant, participation of local and Indigenous communities in HWC mitigation activities produces better conservation outcomes. Centering communities in the ideation, implementation, and evaluation of HWC mitigation promotes more equitable and sustainable management strategies for long‐term human–wildlife coexistence.

The activities of the methanolic extract of Eranthemum roseum on biological functions: antioxidants, anti-proliferative, anti-inflammatory, anti-diabetic, ADMET and in silico studies - Ramachandran Adhavan; Kuppusamy Selvam; Palanisamy Prakash; Dharmalingam Kirubakaran; Muthugounder Subramanian Shivakumar (Vegetos, 2024)

Room temperature ultrasensitive detection of acetone vapours via noble metal anchored reduced graphene oxide - Shilpa M.P.; Shivakumar Jagadish Shetty; Saideep Shirish Bhat; Vikash Mishra; Shreepooja Bhat; Gurumurthy S.C. (Journal of Environmental Chemical Engineering, 2024)

Optimized batch cultivation and scale-up of Bacillus thuringiensis for high-yield production of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) - Lovely; Sanjay Kumar; Ashok Kumar Srivastava; Srividya Shivakumar (Bioresource Technology, 2024)

A facile microwave assisted synthesis of thymohydroquinone with antibiofilm properties against Salmonella typhi and Listeria monocytogenes - Drishya P.K; Prachi A. Patra; Anil Kumar K; Shivakumar L; Sarma Mutturi; Nagarajan S (Food Bioscience, 2024)

Phase-Field Based Peridynamics Implementation to Model Blast-Induced Fracture in Brittle Solids - Anirban Mondal; Anil Pathrikar; Shivakumar Karekal (Rock Mechanics and Rock Engineering, 2024)

A comprehensive review of the mechanical separation of waste printed circuit boards - Surya Kanta Das; G. Ellamparuthy; Tonmoy Kundu; Shivakumar I. Angadi; Swagat S. Rath (Process Safety and Environmental Protection, 2024)

Entomopathogenic fungi promising biocontrol agents for managing lepidopteran pests: Review of current knowledge - Sengodan Karthi; Prabhakaran Vasantha-Srinivasan; Sengottayan Senthil-Nathan; Yeon Soo Han; Muthugounder Subramanian Shivakumar; Ramasamy Kanagaraj Murali-Baskaran; Kandaswamy Kalaivani; Narayanaswamy Radhakrishnan; Ki Beom Park; Guilherme Malafaia (Biocatalysis and Agricultural Biotechnology, 2024)

Synergistic applications of nanostructured boron nitride in photocatalysis and targeted drug delivery - Priyadarshani Shivakumar Mali; Bhagyashree Krishnarao Jagtap; Dankan Gowda V; B Ashreetha; G U Vasanthakumar; Mandeep kaur; Venkatesan Hariram (Nanotechnology for Environmental Engineering, 2024)

Predictive power of YREMs and BLUPs for selecting superior genotypes in perennial crops: A black pepper case study - Mundagodu S. Shivakumar; Nagenahalli C. Sunitha; Hosahalli J. Akshitha; Koryampalli V. Saji; Sasikumar B. Pillai (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Do rainfed production systems have lower environmental impact over irrigated production systems?: On -farm mitigation strategies - G. Pratibha; I. Srinivas; B.M.K. Raju; S. Suvana; K.V. Rao; M. Srinivasa Rao; Anamika Jha; Shivakumar Anna; M. Prabhakar; V.K. Singh; Adlul Islam; Rajbir Singh; et al. (Science of The Total Environment, 2024)

Application of sequential design for enhanced l-asparaginase synthesis from Ganoderma australe GPC191 - Meghna Chakraborty; Srividya Shivakumar (World Journal of Microbiology and Biotechnology, 2024)

Biological and molecular characterization of begomovirus and its DNA satellites associated with leaf curl disease of zinnia in India - C. Shivakumar; V. Venkataravanappa; H. K. Ramappa; W. A. R. T. Wickramaarachchi; K. T. Rangaswamy; Shridhar Hiremath; H. D. Vinaykumar; C. N. Lakshminarayana Reddy; K. S. Shankarappa (Indian Phytopathology, 2024)

Climate-smart deficit irrigation and nutrient management strategies to conserve energy, greenhouse gas emissions, and the profitability of fodder maize seed production - Hanamant M. Halli; Prabhu Govindasamy; V.K. Wasnik; B.G. Shivakumar; Sunil Swami; Mukesh Choudhary; V.K. Yadav; A.K. Singh; N. Raghavendra; Venkadasamy Govindasamy; Amaresh Chandra; K. Sammi Reddy (Journal of Cleaner Production, 2024)

Mechanistic insights and DFT analysis of bimetal doped styrofoam-like LaFeO3 perovskites with in-built dual redox couples for enhanced Photo-Fenton degradation of Tetracycline - Anupriya James; Shivakumar; John D Rodney; Sindhur Joshi; Udayakumar Dalimba; Byung Chul Kim; N.K. Udayashankar (Chemical Engineering Journal, 2024)

Cadmium as an Endocrine Disruptor That Hinders the Reproductive and Developmental Pathways in Freshwater Fish: A Review - Kaakarlu Shivakumar Vinanthi Rajalakshmi; Wen-Chao Liu; Balasubramanian Balamuralikrishnan; Arun Meyyazhagan; Govindharajan Sattanathan; Manikantan Pappuswamy; Kadanthottu Sebastian Joseph; Kuppusamy Alagesan Paari; Jang-Won Lee (Fishes, 2023)
Cadmium (Cd) is a non-essential element with sub-lethal effects even at low concentrations. The persistent nature of Cd and its tendency to bioaccumulate eventually create harmful effects on water biota, including fish. Cd affects various aspects of hormonal action in fish since it bioaccumulates in the endocrine system and hinders the synthesis, secretion, and metabolic activity of hormones, causing severe damage along the hypothalamus–pituitary–gonadal axis. Linking reproductive and developmental impairments in fish with ecologically relevant concentrations of individual metals can be challenging due to the complexity of aquatic ecosystems. This review deliberated the significant and novel trends of toxicological difficulties and approaches, including elucidating environmental sources’ bioavailability and Cd-induced toxic effects in freshwater fish. Both acute and chronic exposure to Cd can cause a range of adverse effects, such as growth inhibition, impaired reproductive capacity, endocrine disruption, and developmental abnormalities in freshwater fish, as evidenced by the present review. These investigations support the concept of Cd as a naturally available pollutant that causes irreversible damage in fish. These findings will help to understand the etiology of environmental circumstances that pose substantial dangers to fish health and are also crucial for preventing and treating exposure-related reproductive disturbances in freshwater fish due to environmental pollution.

Hydrodynamic performance of wave energy converter integrated with pile restrained floating structure near a partially reflecting seawall - Shivakumar B. Patil; D. Karmakar (Ocean Engineering, 2023)

In-vitro antibacterial, antioxidant and anti-inflammatory and In-silico ADMET, molecular docking study on Hardwickia binata phytocompunds with potential inhibitor of skin cancer protein - Peraman Manimegalai; Kuppusamy Selvam; Palanisamy Prakash; Dharmalingam Kirubakaran; Muthugounder Subaramanian Shivakumar; Sengottayan SenthilNathan (In Silico Pharmacology, 2023)

A hyperspectral evaluation approach for quantifying salt-induced weathering of sandstone - Haiqing Yang; Chiwei Chen; Jianghua Ni; Shivakumar Karekal (Science of The Total Environment, 2023)

Modelling the impacts of carbon pricing in India’s power system using a dynamic optimization approach - Liliana E. Benitez; Maarten Brinkerink; Abhishek Shivakumar; Paul Deane (The Electricity Journal, 2023)

Continuous Manufacturing of Oil in Water (O/W) Emulgel by Extrusion Process - V. Anusha Echanur; Anusha V. Matadh; S. G. Pragathi; S. Sarasija; Yeoh Thean; Abu Zayed Badruddoza; Jaymin Shah; Vijay Kulkarni; Srinivas Ajjarapu; N. M. Reena; H. N. Shivakumar; S. Narasimha Murthy (AAPS PharmSciTech, 2023)

A multi-metric fish index to measure the ecological quality of tropical predominantly open estuaries along the western coast of India - Sreekanth Giri Bhavan; Sajiya Mujawar; Shivakumar Haragi; Jagannath Rathod; Baban Ingole; Trivesh Mayekar; Dhanya Mohan Lal; Sri Hari Murugesan; Kiranya Bella; Bijukumar Appukuttannair; Pramila Sahadevan; Ranjeet Kutty; et al. (Environmental Monitoring and Assessment, 2023)

Bioprospecting of Metarhizium anisopliae derived crude extract: a ecofriendly insecticide against insect pest - P. Vivekanandhan; K. Swathy; Stefano Bedini; M. S. Shivakumar (International Journal of Tropical Insect Science, 2023)

Largescale mortality of Oreochromis mossambicus in lakes and reservoirs of Karnataka due to coinfection of Tilapia Lake virus (TiLV) and multidrug-resistant Aeromonas veronii: An emerging fish disease in India - T. Suresh; M.S. Nithin; K.B. Kushala; S.K. Girisha; V.B. Shivakumar; S.B. Dheeraj; T.G. Puneeth; K. Kishan; T.N. Vinay (Aquaculture, 2023)

Development, validation and application of RP-HPLC method for quantitative estimation of wedelolactone in different accessions and plant parts of Eclipta alba (L.) - B. Anil Kumar; V. K. Rao; K. Hima Bindu; M. R. Rohini; Shivakumar (Journal of Plant Biochemistry and Biotechnology, 2022)

Biogenic synthesis of ZnO nanoparticles mediated from Borassus flabellifer (Linn): antioxidant, antimicrobial activity against clinical pathogens, and photocatalytic degradation activity with molecular modeling - Dharman Kalaimurugan; Kandhasamy Lalitha; Kaliannan Durairaj; Palaniappan Sivasankar; Sungkwon Park; Kannan Nithya; Muthugoundar Subramanian Shivakumar; Wen-Chao Liu; Balasubramanian Balamuralikrishnan; Srinivasan Venkatesan (Environmental Science and Pollution Research, 2022)

Polymer-Coated Polymeric (PCP) Microneedles for Controlled Dermal Delivery of 5-Fluorouracil - Anusha V. Matadh; Deeksha Jakka; S. G. Pragathi; Srinath Rangappa; H. N. Shivakumar; Howard Maibach; N. M. Reena; S. Narasimha Murthy (AAPS PharmSciTech, 2022)

Effect of host plants nutrients, antioxidants, and phytochemicals on growth, development, and fecundity of Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae) - Govindaraj Vengateswari; Murugan Arunthirumeni; Muthugounder Subramaniam Shivaswamy; Muthugounder Subramanian Shivakumar (International Journal of Tropical Insect Science, 2022)

Stability of insecticidal molecule aucubin and their toxicity on Anopheles stephensi, Aedes aegypti, Culex quinquefasciatus and Artemia salina - P. Vivekanandhan; K. Swathy; M. S. Shivakumar (International Journal of Tropical Insect Science, 2022)

Biosynthesis and characterization of silver nanoparticles from symbiotic bacteria Xenorhabdus nematophila and testing its insecticidal efficacy on Spodoptera litura larvae - Kandhasamy Lalitha; Kannan Nithya; Srinivasan Venkatesan; Muthugounder Subramanian Shivakumar (BioMetals, 2022)

Influence of fuel system variations on performance and emission characteristics of combined air-wall-guided mode modified GDI engine with alcoholic fuels and exhaust gas recirculation - Shivakumar Nagareddy; Kumaresan Govindasamy (Environmental Science and Pollution Research, 2022)

Improvement of Strength-Deformability Behaviour of Rock-Like Materials and Coal Using Fibre-Reinforced Thin Spray-on Liner (FR-TSL) - Gopi Krishna Dondapati; Debasis Deb; Ian Porter; Shivakumar Karekal (Rock Mechanics and Rock Engineering, 2022)

Convective Solvent Transport Pathways for Absorption of Drugs from Topical Formulation - Abhijeet Maurya; Jungeun Bae; Vanaja Kenchappa; H. N. Shivakumar; Howard Maibach; Michael A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2022)

Identification of insecticidal molecule aucubin from Metarhizium anisopliae ethyl acetate crude extract against disease mosquito vector - P. Vivekanandhan; K. Swathy; M. S. Shivakumar (International Journal of Tropical Insect Science, 2022)

Application of encapsulated nano materials as feed additive in livestock and poultry: a review - Duraisamy Rajendran; Preedia Babu Ezhuthupurakkal; Rithu Lakshman; Nisarani Kollurappa Shivakumar Gowda; Ayyasamy Manimaran; Somu BN Rao (Veterinary Research Communications, 2022)

An Optimization Methodology of Cutter-Spacing for Efficient Mechanical Breaking of Jointed Rock Mass - Kanglei Song; Haiqing Yang; Junning Xie; Shivakumar Karekal (Rock Mechanics and Rock Engineering, 2022)

Non-dermal applications of microneedle drug delivery systems - Apoorva Panda; V. Anusha Matadh; Sarasija Suresh; H. N. Shivakumar; S. Narasimha Murthy (Drug Delivery and Translational Research, 2022)

Peroxidase activity as a marker to evaluate resistance in Black pepper against Phytophthora infection - R. Suseela Bhai; Riya Alex; P. Vadivukkarasi; M. S. Shivakumar (Indian Phytopathology, 2021)

Mycobacterium tuberculosis strain lineage in mixed tribal population across India and Andaman Nicobar Island - Azger Dusthackeer; Ashok Kumar; Sucharitha Kannappan Mohanvel; B. Mahizhaveni; S. Shivakumar; S. Raghavi; S. Azhagendran; S. Vetrivel; Vikas Gangadhar Rao; Rajiv Yadav; Vijayachari Paluru; Anil Jacob Purthy; et al. (World Journal of Microbiology and Biotechnology, 2021)

Effect of boron supplementation on laying performance of White Leghorn hens fed diet with and without adequate level of calcium - Vijay Adarsh; Pal Dintaran; Gowda N. K. Shivakumar; Elangovan A. Vijayarangam; Dey Debpriyo Kumar; Kurni Nagaraj; Jadhav S. Eknath (Tropical Animal Health and Production, 2021)

Novel role of photoinsensitive alleles in adaptation of soybean [Glycine max (L.) Merr.] to rainfed short growing seasons of lower latitudes - Rachana Tripathi; Nisha Agrawal; Giriraj Kumawat; Sanjay Gupta; Mrinal Kuchlan; Shivakumar Maranna; Vennampally Nataraj; Punam Kuchlan; Gyanesh K. Satpute; Milind B. Ratnaparkhe; Vangala Rajesh; Subhash Chandra; et al. (Genetic Resources and Crop Evolution, 2021)

Cephalosporium curvulum lectin causes mycotic keratitis by initiating infection through MyD88 dependent cellular proliferation and apoptosis in human corneal epithelial cells - Narasimhappagari Jagadeesh; Shivakumar Belur; Suhas Ballal; Sanhita Roy; Shashikala R. Inamdar (Glycoconjugate Journal, 2021)

Identification of novel genetic sources for agronomic and quality traits in soybean using multi-trait allele specific genic marker assays - Giriraj Kumawat; Shivakumar Maranna; Sanjay Gupta; Rachana Tripathi; Nisha Agrawal; Vijayata Singh; Vangala Rajesh; Subhash Chandra; Viraj Kamble; Vennampally Nataraj; Abhishek Bharti; Mahaveer P. Sharma; et al. (Journal of Plant Biochemistry and Biotechnology, 2021)

Identification and characterization of a novel long juvenile resource AGS 25 - Sanjay Gupta; Giriraj Kumawat; Soniya Yadav; Rachana Tripathi; Nisha Agrawal; Shivakumar Maranna; Gyanesh K. Satpute; Gireesh Channappa; Mamta Arya; Sayed M. Husain; Virender S. Bhatia; Nanita Devi; et al. (Genetic Resources and Crop Evolution, 2021)

Identification of potential donors and QTLs for resistance to false smut in a subset of rice diversity panel - Shridhar Shivakumar Hiremath; Dharminder Bhatia; Jyoti Jain; Mandeep Singh Hunjan; Rupinder Kaur; Najam Waris Zaidi; Uma Shankar Singh; Bo Zhou; Jagjeet Singh Lore (European Journal of Plant Pathology, 2021)

QTL mapping for long juvenile trait in soybean accession AGS 25 identifies association between a functional allele of FT2a and delayed flowering - Rachana Tripathi; Nisha Agrawal; Giriraj Kumawat; Sanjay Gupta; Philips Varghese; Milind B. Ratnaparkhe; Virender S. Bhatia; Shivakumar Maranna; Gyanesh K. Satpute; Suresh Chand; Meeta Jain (Euphytica, 2021)

Correction to: Recent progress on engineering microbial alginate lyases towards their versatile role in biotechnological applications - Shivakumar Renuka Dharani; Ramachandran Srinivasan; Regunathan Sarath; Mohandass Ramya (Folia Microbiologica, 2021)

Correction to: Elucidating the processes and pathways enriched in buffalo sperm proteome in regulating semen quality - Bala Krishnan Binsila; Santhanahalli Siddalingappa Archana; Laxman Ramya; Divakar Swathi; Sellappan Selvaraju; NK. Shivakumar Gowda; Din Taran Pal; Abu Rafay; Raghavendra Bhatta (Cell and Tissue Research, 2021)

Elucidating the processes and pathways enriched in buffalo sperm proteome in regulating semen quality - Bala Krishnan Binsila; Santhanahalli Siddalingappa Archana; Laxman Ramya; Divakar Swathi; Sellappan Selvaraju; NK. Shivakumar Gowda; Din Taran Pal; Abu Rafay; Raghavendra Bhatta (Cell and Tissue Research, 2021)

Recent progress on engineering microbial alginate lyases towards their versatile role in biotechnological applications - Shivakumar Renuka Dharani; Ramachandran Srinivasan; Reghunathan Sarath; Mohandass Ramya (Folia Microbiologica, 2020)

Comparative efficacy of Eucalyptus globulus (Labill) hydrodistilled essential oil and temephos as mosquito larvicide - Perumal Vivekanandhan; Ayyakkannu Usha-Raja-Nanthini; Gurusamy Valli; Muthugoundar Subramanian Shivakumar (Natural Product Research, 2020)

Multivariate statistics and water quality index (WQI) approach for geochemical assessment of groundwater quality—a case study of Kanavi Halla Sub-Basin, Belagavi, India - Venkanagouda Bhimanagouda B Patil; Shannon Meryl Pinto; Thejashree Govindaraju; Virupaksha Shivakumar Hebbalu; Vignesh Bhat; Lokesh Nanjappa Kannanur (Environmental Geochemistry and Health, 2020)

Genetic inheritance and identification of germplasm sources for anthracnose resistance in soybean [Glycine max (L.) Merr.] - Vennampally Nataraj; Shivakumar Maranna; Giriraj Kumawat; Sanjay Gupta; Laxman Singh Rajput; Sanjeev Kumar; Amar Nath Sharma; Virender Singh Bhatia (Genetic Resources and Crop Evolution, 2020)

Potentiometric polyphenol oxidase biosensor for sensitive determination of phenolic micropollutant in environmental samples - Shivamurthy Ravindra Yashas; Shadakshari Sandeep; Ballagere Puttaraju Shivakumar; Ningappa Kumara Swamy (Environmental Science and Pollution Research, 2020)

A core fucose specific lectin from Cephalosporium curvulum induces cellular apoptosis in hepatocellular and pancreatic cancer cells and effective in detecting AFP - Shivakumar Belur; Narasimhappagari Jagadeesh; Bale M. Swamy; Shashikala R. Inamdar (Glycoconjugate Journal, 2020)

Privacy Concerns About Personal Health Information and Fear of Unintended Use of Biospecimens Impact Donations by African American Patients - Arthi Reddy; Abhimanyu Amarnani; Michael Chen; Sophia Dynes; Bryan Flores; Ariella Moshchinsky; Yeon Joo Lee; Vadim Kurbatov; Iuliana Shapira; Shivakumar Vignesh; Laura Martello (Journal of Cancer Education, 2020)

Biological effects of Avicennia marina (Forssk.) vierh. extracts on physiological, biochemical, and antimicrobial activities against three challenging mosquito vectors and microbial pathogens - Sengodan Karthi; Manohar Vinothkumar; Uthirarajan Karthic; Venkatesan Manigandan; Ramachandran Saravanan; Prabhakaran Vasantha-Srinivasan; Chinnaperumal Kamaraj; Muthugounder S. Shivakumar; Surajit De Mandal; Arumugam Velusamy; Patcharin Krutmuang; Sengottayan Senthil-Nathan (Environmental Science and Pollution Research, 2020)

Acoustic emission investigation on scale effect and anisotropy of jointed rock mass by the discrete element method - Zhaohui Chong; Qiangling Yao; Xuehua Li; Karekal Shivakumar (Arabian Journal of Geosciences, 2020)

Effect of Temperature, Humidity and Light Intensity on Micropropagated Sugarcane (Saccharum Species Hybrid) Genotypes - Suresh Yadav; T. E. Nagaraja; H. C. Lohithaswa; K. V. Shivakumar (Sugar Tech, 2020)

Isolation and characterization of heavy-metal-resistant bacteria and their applications in environmental bioremediation - D. Kalaimurugan; B. Balamuralikrishnan; K. Durairaj; P. Vasudhevan; M. S. Shivakumar; T. Kaul; S. W. Chang; B. Ravindran; S. Venkatesan (International Journal of Environmental Science and Technology, 2020)

Effect of Water Content on Argillization of Mudstone During the Tunnelling process - Bolong Liu; Haiqing Yang; Shivakumar Karekal (Rock Mechanics and Rock Engineering, 2020)

The maize α-zein promoter can be utilized as a strong inducer of cellulase enzyme expression in maize kernels - Deborah Vicuna Requesens; Maria Elena Gonzalez Romero; Shivakumar P. Devaiah; Yeun-Kyung Chang; Ashley Flory; Stephen Streatfield; Rebecca Ring; Cassie Phillips; Nathan C. Hood; Cyrus Dean Marbaniang; John A. Howard; Elizabeth E. Hood (Transgenic Research, 2019)

Differentiation potential of different regions-derived same donor human Wharton’s jelly mesenchymal stem cells into functional smooth muscle-like cells - Dinesh Bharti; Sharath Belame Shivakumar; Young-Bum Son; Young-Ho Choi; Imran Ullah; Hyeon-Jeong Lee; Eun-Jin Kim; Sun-A Ock; Ji-Eun Park; Ji-Kwon Park; Dawon Kang; Sung-Lim Lee; et al. (Cell and Tissue Research, 2019)

Intra-line uniformity and inter-line variability of doubled haploid rice lines under different environmental conditions - Debina Sanasam; M. Udaya Kumar; N. Shivakumar; B. Mohan Raju (Plant Physiology Reports, 2019)

Genetic relationship, population structure analysis and allelic characterization of flowering and maturity genes E1, E2, E3 and E4 among 90 Indian soybean landraces - Giriraj Kumawat; Arti Yadav; Gyanesh K. Satpute; C. Gireesh; Rakesh Patel; M. Shivakumar; Sanjay Gupta; Suresh Chand; Virender Singh Bhatia (Physiology and Molecular Biology of Plants, 2019)

Vertical Distribution of Macrobenthos in Hypoxia-Affected Sediments of the Northern Gulf of Mexico: Applying Functional Metrics - Shivakumar K. Shivarudrappa; Chet F. Rakocinski; Kevin B. Briggs (Estuaries and Coasts, 2019)

Mesenchymal Stem Cells of Different Origin-Seeded Bioceramic Construct in Regeneration of Bone Defect in Rabbit - Swapan Kumar Maiti; M. U. Shivakumar; Divya Mohan; Naveen Kumar; Karam Pal Singh (Tissue Engineering and Regenerative Medicine, 2018)

Paraventricular hypothalamic and amygdalar CRF neurons synapse in the external globus pallidus - Albert J. Hunt; Rajan Dasgupta; Shivakumar Rajamanickam; Zhiying Jiang; Michael Beierlein; C. Savio Chan; Nicholas J. Justice (Brain Structure and Function, 2018)

Comparative analysis of human Wharton’s jelly mesenchymal stem cells derived from different parts of the same umbilical cord - Dinesh Bharti; Sharath Belame Shivakumar; Ji-Kwon Park; Imran Ullah; Raghavendra Baregundi Subbarao; Ji-Sung Park; Sung-Lim Lee; Bong-Wook Park; Gyu-Jin Rho (Cell and Tissue Research, 2018)

Probabilistic seismic hazard at the archaeological site of Gol Gumbaz in Vijayapura, south India - Shivakumar G Patil; Arun Menon; G R Dodagoudar (Journal of Earth System Science, 2018)

Mutational analysis of substrate specificity in a Citrus paradisi flavonol 3-O-glucosyltransferase - Shivakumar P. Devaiah; Benjamin M. Tolliver; Cheng Zhang; Daniel K. Owens; Cecilia A. McIntosh (Journal of Plant Biochemistry and Biotechnology, 2018)

Mitogenic lectins from Cephalosporium curvulum (CSL) and Aspergillus oryzae (AOL) mediate host–pathogen interactions leading to mycotic keratitis - Suhas Ballal; Shivakumar Belur; Preeti Laha; Sanhita Roy; B. M. Swamy; Shashikala R. Inamdar (Molecular and Cellular Biochemistry, 2017)

Splitter plate as a flow-altering pier scour countermeasure - Shivakumar Khaple; Prashanth Reddy Hanmaiahgari; Roberto Gaudio; Subhasish Dey (Acta Geophysica, 2017)

Trans-ungual Delivery of AR-12, a Novel Antifungal Drug - Avadhesh Singh Kushwaha; P. Sharma; H. N. Shivakumar; C. Rappleye; A. Zukiwski; S. Proniuk; S. Narasimha Murthy (AAPS PharmSciTech, 2017)

Interference of an upstream pier on local scour at downstream piers - Shivakumar Khaple; Prashanth Reddy Hanmaiahgari; Roberto Gaudio; Subhasish Dey (Acta Geophysica, 2017)

Insecticidal potential of Ocimum canum plant extracts against Anopheles stephensi, Aedes aegypti and Culex quinquefasciatus larval and adult mosquitoes (Diptera: Culicidae) - Jimmantiyur Madhappan Murugan; Govindaraju Ramkumar; Muthugoundar Subramanian Shivakumar (Natural Product Research, 2016)

Over-expression of the cucumber expansin gene (Cs-EXPA1) in transgenic maize seed for cellulose deconstruction - Sangwoong Yoon; Shivakumar P. Devaiah; Seo-eun Choi; Jeff Bray; Robert Love; Jeffrey Lane; Carol Drees; John H. Howard; Elizabeth E. Hood (Transgenic Research, 2016)

Exquisite specificity of mitogenic lectin from Cephalosporium curvulum to core fucosylated N-glycans - Shashikala R. Inamdar; Sachin M. Eligar; Suhas Ballal; Shivakumar Belur; Rajiv D. Kalraiya; Bale M. Swamy (Glycoconjugate Journal, 2016)

In silico prediction of epitopes for Chikungunya viral strains - Priyanka Kori; Shrishailnath S. Sajjan; Shivakumar B. Madagi (Journal of Pharmaceutical Investigation, 2015)

Two dimensional quantitative structure activity relationship models for 5alpha-reductase type 2 inhibitors - Urvashi Balekundri; Shrishailnath S. Sajjan; Shivakumar B. Madagi (Journal of Pharmaceutical Investigation, 2015)

Assessment of field-grown cellulase-expressing corn - Martina Garda; Shivakumar P. Devaiah; Deborah Vicuna Requesens; Yeun-Kyung Chang; Audrei Dabul; Christy Hanson; Kendall R. Hood; Elizabeth E. Hood (Transgenic Research, 2015)

Study on evaluation of silage from pineapple (Ananas comosus) fruit residue as livestock feed - Nisarani Kollurappa Shivakumar Gowda; Naglapura Chandrashekara Vallesha; Vaibhav Bhagvan Awachat; Samireddypalli Anandan; Din Taran Pal; Cadaba Srinivasa Prasad (Tropical Animal Health and Production, 2015)

Design and Optimization of Curcumin–HPβCD Bioadhesive Vaginal Tablets by 23 Factorial Design: In Vitro and In Vivo Evaluation - Umme Hani; H. G. Shivakumar; Atul Srivastava; Nawaz Mahammed; Shailesh Thirumaleshwar; Naga Sravan kumar Varma; Rudra Vaghela; Chetan G. Shinde; M. P. Gowrav (Journal of Pharmaceutical Innovation, 2015)

Molecular characterization and genetic diversity analysis of soybean (Glycine max (L.) Merr.) germplasm accessions in India - Giriraj Kumawat; Gourav Singh; C. Gireesh; M. Shivakumar; Mamta Arya; Dinesh K. Agarwal; Syed Masroor Husain (Physiology and Molecular Biology of Plants, 2015)

Inhibition of NarL of Mycobacterium Tuberculosis: an in silico approach - K. V. Shivakumar; Prashantha Karunakar; Jhinuk Chatterjee (Interdisciplinary Sciences: Computational Life Sciences, 2014)

Megha-Tropiques: mission planning, analysis, and operations - P. Vijayasree; Naresh Kumar; Ritu Karidhal; K. Harendranath; V. Kesava Raju; S.K. Shivakumar (International Journal of Remote Sensing, 2014)

Evaluation of the neuroprotective effect of chrysin via modulation of endogenous biomarkers in a rat model of spinal cord injury - Amit D. Kandhare; V. Shivakumar; Anuchandra Rajmane; Pinaki Ghosh; Subhash L. Bodhankar (Journal of Natural Medicines, 2014)

Establishing postprandial bio-equivalency and IVIVC for generic metformin sustained release small sized tablets - Chandramohan Eaga; Shivakumar Mantri; Rajkumar Malayandi; Phani Krishna Kondamudi; Sumon Chakraborty; S. V. N. Raju; Deepika Aggarwal (Journal of Pharmaceutical Investigation, 2014)

Heterologous expression of cellobiohydrolase II (Cel6A) in maize endosperm - Shivakumar Pattada Devaiah; Deborah Vicuna Requesens; Yeun-Kyung Chang; Kendall R. Hood; Ashley Flory; John A. Howard; Elizabeth E. Hood (Transgenic Research, 2013)

Enhanced Expression Levels of Cellulase Enzymes Using Multiple Transcription Units - Erin Egelkrout; Karen McGaughey; Todd Keener; Amberlyn Ferleman; Susan Woodard; Shivakumar Devaiah; Zivko Nikolov; Elizabeth Hood; John Howard (BioEnergy Research, 2013)

5-phenyl-1-benzofuran-2-yl derivatives: synthesis, antimicrobial, and antioxidant activity - Chandrashekar Aswathanarayanappa; Eswarappa Bheemappa; Yadav D. Bodke; Venkatesh K. Bhovi; Raghu Ningegowda; M. C. Shivakumar; S. K. Peethambar; Sandeep Telkar (Medicinal Chemistry Research, 2013)

Occurrence of Plasmid-Mediated AmpC β-Lactamases Among Escherichia coli and Klebsiella pneumoniae Clinical Isolates in a Tertiary Care Hospital in Bangalore - B. Sasirekha; Srividya Shivakumar (Indian Journal of Microbiology, 2012)

A method for transient expression in maize endosperm - Deborah Vicuna Requesens; Erin Egelkrout; Shivakumar Devaiah; Elizabeth E. Hood (In Vitro Cellular & Developmental Biology - Plant, 2010)

Genistein abolishes nucleoside uptake by cardiac fibroblasts - Malini S. Pillai; K. Shivakumar (Molecular and Cellular Biochemistry, 2009)

Spectrophotometric method for the determination of chromium (VI) in water samples - P. Nagaraj; N. Aradhana; Anantharaman Shivakumar; Ashwinee Kumar Shrestha; Avinash k Gowda (Environmental Monitoring and Assessment, 2009)

Sensitive spectrophotometric methods for the assessment of nitrite in water sample - P. Nagaraj; J. S. Prakash; Anantharaman Shivakumar; Ashwinee Kumar Shrestha (Environmental Monitoring and Assessment, 2008)

Hypoxia and antioxidants enhance soluble ICAM-1 release from cardiac fibroblasts - S. Sapna; K. Shivakumar (Molecular and Cellular Biochemistry, 2007)

Chlamydomonas reinhardtii, a model system for functional validation of abiotic stress responsive genes - R. Hema; M. Senthil-Kumar; S. Shivakumar; P. Chandrasekhara Reddy; M. Udayakumar (Planta, 2007)

Faithful tissue-specific expression of the human chromosome 21-linked COL6A1 gene in BAC-transgenic mice - Luzhou Xing; Martha Salas; Chyuan-Sheng Lin; Warren Zigman; Wayne Silverman; Shivakumar Subramaniyam; Vundavalli V. Murty; Benjamin Tycko (Mammalian Genome, 2007)

Capture of interplanetary bodies in geocentric orbits and early lunar evolution - Malapaka Shivakumar; N. Bhandari (Journal of Earth System Science, 2005)

Phosphorus Fractionation and Sorption in P-enriched Soils of Norway - B. R. Singh; T. Krogstad; Y. S. Shivay; B. G. Shivakumar; M. Bakkegard (Nutrient Cycling in Agroecosystems, 2005)

Ribonucleases in the Seedlings of Pearl Millet and their Involvement in Resistance Against Downy Mildew Disease - P.D. Shivakumar; N.S. Vasanthi; H.S. Shetty; Viggo Smedegaard-Petersen (European Journal of Plant Pathology, 2000)

Alterations in collagen metabolism and increased fibroproliferation in the heart in cerium-treated rats implications for the pathogenesis of endomyocardial fibrosis - B. Prakash Kumar; K. Shivakumar (Biological Trace Element Research, 1998)

Intestinal Absorption of Ribavirin Is Preferentially Mediated by the Na+-Nucleoside Purine (Nl) Transporter - Shivakumar D. Patil; Leock Y. Ngo; Paul Glue; Jashvant D. Unadkat (Pharmaceutical Research, 1998)

Isozyme Diversity in Indian Primitive Maize Landraces - K. V. Bhat; K. P. S. Chandel; T. M. Shivakumar; J. K. S. Sachan (Journal of Plant Biochemistry and Biotechnology, 1998)

Depressed antioxidant defense in rat heart in experimental magnesium deficiency implications for the pathogenesis of myocardial lesions - B. Prakash Kumar; K. Shivakumar (Biological Trace Element Research, 1997)

Cerium stimulates protein biosynthesis in rat heart in vivo - B. Prakash Kumar; Sunita L. D'Souza; K. Shivakumar; K. Rathinam (Biological Trace Element Research, 1995)